2019
DOI: 10.2147/prbm.s179838
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quality of life, self-stigma, and coping strategies in patients with neurotic spectrum disorders: a cross-sectional study</p>

Abstract: BackgroundModern psychiatry focuses on self-stigma, coping strategies, and quality of life (QoL). This study looked at relationships among severity of symptoms, self-stigma, demographics, coping strategies, and QoL in patients with neurotic spectrum disorders.MethodsA total of 153 clinically stable participants who met criteria for generalized anxiety disorder, social phobia, panic disorder, agoraphobia, mixed anxiety–depressive disorder, adjustment disorders, somatoform disorders, or obsessive–compulsive diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
33
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 69 publications
7
33
2
1
Order By: Relevance
“…The most important finding of the present study is that the internalised stigma had a significant negative correlation with the current medication adherence, which confirms our research hypothesis. This finding is consistent with several other studies 2 26–28 31. So, it could be said that internalised stigma is an important factor which affects medication adherence in patients with OCD.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The most important finding of the present study is that the internalised stigma had a significant negative correlation with the current medication adherence, which confirms our research hypothesis. This finding is consistent with several other studies 2 26–28 31. So, it could be said that internalised stigma is an important factor which affects medication adherence in patients with OCD.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also showed that the current severity of OCD symptoms was significantly negatively correlated with medication adherence, possibly suggesting that medication non-compliance is linked to increased severity of disorder, although direction of causality is difficult to establish from the available data. The findings are consistent with other studies showing negative correlation between severity of disorder and medication adherence 2 27 28…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations